How to restore your voice? - rehabilitation methods after laryngectomy - Borowik, Joanna; Brodowski, Wojciech; Basta-Arciszewska, Katarzyna; Pawłowski, Piotr; Swora, Aleksandra; Żelazny, Przemysław; Bróż, Sebastian; Sygacz, Oliwer; Filipczak, Joanna; Dankiewicz, Sara (Journal of Education, Health and Sport, 2022)
Introduction: The voice is an unique communication tool, characteristic of each person alone. Lacking the ability to communicate through it, can negatively affect mental health. It turns out that voice and speech rehabilitation after surgery is widely used and allows patients to improve their functioning, giving them a chance to live a normal life. Aim of the study: The purpose of the study was to review the knowledge of voice and speech rehabilitation options for patients after laryngectomy and the results of the methods used. The text is intended to educate professionals and patients who are undergoing surgical treatment and experience concerns about their future functioning. Materials and Methods: Scientific articles were reviewed using the PubMed database using the keywords: voice rehabilitation; total laryngectomy; speech disorders. State of the art: Prevalent methods of voice and speech rehabilitation in patients after total laryngectomy include the teaching of esophageal speech, tracheoesophageal speech and the use of an artificial larynx. Of these, esophageal speech appears to be the least effective method. Under certain circumstances, an artificial larynx may be the optimal choice among certain groups of patients. Numerous studies cited prove tracheoesophageal speech to achieve the best results measurable by commonly used indicators. Summary: Total laryngectomy is not a sentence for patients. Effective rehabilitation significantly improves the quality of life and communication. It is difficult to unequivocally indicate which method of voice and speech rehabilitation is most beneficial for patients - the choice should be tailored to the individual and its preferences and chances. In his work, the specialist should seek a compromise between obtaining the best acoustic results and acceptance of the method by the patient.